2004
DOI: 10.1177/0145445503259830
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Psychopathology in Individuals with Developmental Disabilities

Abstract: Individuals with developmental disabilities are at high risk for developing mental health problems. The prevalence of psychopathology is approximately 4 times higher than that found in the general population. Yet there is a tendency to underdiagnose psychiatric disorders in the developmentally delayed population because of diagnostic overshadowing, the lack of appropriate diagnostic criteria, and the paucity of appropriate assessment measures. Over the past decade, there has been an emergence of scales develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 38 publications
0
46
0
5
Order By: Relevance
“…In contrast, behaviors which result in significant impairment in learning or socialization or any dangerous behavior are a cause for concern at any age. [Dykens, 2000;Rush et al, 2004]. One of the most widely used instruments for the assessment of persons with cognitive impairment and maladaptive behavior is the Aberrant Behavior Checklist (ABC) [Aman et al, 1985].…”
Section: Behavioral Style and Common Concerns In Young Children With mentioning
confidence: 99%
“…In contrast, behaviors which result in significant impairment in learning or socialization or any dangerous behavior are a cause for concern at any age. [Dykens, 2000;Rush et al, 2004]. One of the most widely used instruments for the assessment of persons with cognitive impairment and maladaptive behavior is the Aberrant Behavior Checklist (ABC) [Aman et al, 1985].…”
Section: Behavioral Style and Common Concerns In Young Children With mentioning
confidence: 99%
“…Mental health problems in the DD population often go unrecognized and undertreated due to communication issues (Rush, Bowman, Eidman, Toole, & Mortenson, 2004;Valk & Walsh, 2008), masked symptoms (Valk & Walsh, 2008), and inadequacies within the diagnostic system (Rush et al, 2004). Nevertheless, researchers have found that 31-41% of the DD population also suffers from mental illness (Einfeld et al, 2006;Tonge & Einfeld, 2000), a prevalence about 4 times higher than that of the general non-DD population (Koller, Richardson, Katz, & McLaren, 1982;Tonge & Einfeld, 2000).…”
mentioning
confidence: 99%
“…four to five times higher than in the general population (Rush, Bowman, Eidman, Toole, & Mortenson, 2004). Autism, selfinjurious behaviours, attention deficit hyperactivity disorder, anxiety, depression and psychosis are very frequent .…”
mentioning
confidence: 88%